2018
DOI: 10.3892/ijmm.2018.3438
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive unfolded protein response promotes cell survival in rifampicin-treated L02 cells

Abstract: An important concept in drug-induced liver injury (DILI) is adaptation, which means the injury reverses with the continuation of the drug. The mechanism of adaption of drugs remains enigmatic, adaptive unfolded protein response (UPR) is possibly involved. We once observed adaptation phenomenon of rifampicin (RFP) in animal models, in this study, we investigate the effects of RFP on adaptive UPR in L02 cells, and after inhibiting UPR by using 4-phenylbutyrate (4-PBA), the change of cell viability and cell apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“… 11 Induction of an adaptive UPR is a protective mechanism, shielding cells against injury. 19 However, overactivation or chronic prolongation of UPR may lead to apoptosis and loss of hepatocytes. 10 Several pathways can contribute to ER stress-mediated apoptosis, including inositol-requiring enzyme 1α (IRE1α), apoptosis signal-regulating kinase 1, c-Jun N-terminal kinases signaling, CHOP regulation of B cell lymphoma 2 (BCL2) protein family members and apoptotic genes, ER-localized BCL2-associated X protein, BCL2 homologous antagonist killer, and glycogen synthase kinase 3β (GSK3β).…”
Section: Discussionmentioning
confidence: 99%
“… 11 Induction of an adaptive UPR is a protective mechanism, shielding cells against injury. 19 However, overactivation or chronic prolongation of UPR may lead to apoptosis and loss of hepatocytes. 10 Several pathways can contribute to ER stress-mediated apoptosis, including inositol-requiring enzyme 1α (IRE1α), apoptosis signal-regulating kinase 1, c-Jun N-terminal kinases signaling, CHOP regulation of B cell lymphoma 2 (BCL2) protein family members and apoptotic genes, ER-localized BCL2-associated X protein, BCL2 homologous antagonist killer, and glycogen synthase kinase 3β (GSK3β).…”
Section: Discussionmentioning
confidence: 99%
“…As the concentration of AP or RFP increased and the treatment time was prolonged, the cell viability decreased in a dose-and time-dependent manner (Figure 1a,b). The IC50 values for RFP were reported to be 548.91 and 234.96 µM in 24 and 48 hr, respectively, in LO2 cells (Zhang & Xu, 2018). Other studies found that the IC50 value for RFP in 24 hr was 530.33 µM and established cell injury model by treatment with 10 mM AP for 24 hr (Wu et al, 2016; Yuan-Jing, Wei, Jian-Ping, Yu-Xia, & Zi-Ling, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…hy926 cell lines and the microfluidic device mentioned earlier, and the fabrication process and materials formula used in this study were the same with our previous study. As an immortalized hepatocyte line, L-02 cells have been proven to be suitable for toxicity assessments and bioartificial liver establishment ( Kouam et al, 2017 ; Zhang and Xu, 2018 ). In this study, we designed four control systems, i.e., two-dimensional co-culture (2D), collagen sandwich co-culture (CS), 3D hybrid hydrogel fiber (3D-H) co-culture systems and primary human hepatocytes (PHHs).…”
Section: Introductionmentioning
confidence: 99%